Lying on misleading information: false confirmation leads to memory errors - Battista, Fabiana (Psychology, crime & law, 2025)
Research on post-event misinformation demonstrated that being exposed to such information can undermine people’s memory for the original event. Similarly, studies on lying and memory showed that lying upon an event can negatively impact memory. We asked participants to read a case vignette about an accident, and answered some questions on true and misleading details. Participants either lied (i.e. liars group) or told the truth (i.e. truth-tellers group) about false misleading (distorted: details partially false and fabricated: completely false details compared to the ones in the case-vignette) information (Experiment 1). In Experiment 2, an additional group of participants was included who did not perform the lying/truth-telling phase (i.e. delayed test group). After 1-week, all participants genuinely recalled the case vignette and provided their beliefs for its occurrence. Liars reported more fabricated information than truth-tellers (Experiment 1). The delayed test group reported fewer correct information than the other groups while liars reported more memory errors than the former (Experiment 2). Also, liars reported lower recollection and belief ratings than truth-tellers (Experiment 1), while the delayed test group reported lower recollection and beliefs than both liars and truth-tellers (Experiment 2). Overall, our findings showed that lying on misinformation results in memory errors.